RIG-1-Like Receptor Activation Synergizes With Intratumoral Alpha Radiation to Induce Pancreatic Tumor Rejection, Triple-Negative Breast Metastases Clearance, and Antitumor Immune Memory in Mice - Domankevich, Vered; Efrati, Margalit; Schmidt, Michael; Glikson, Eran; Mansour, Fairuz; Shai, Amit; Cohen, Adi; Zilberstein, Yael; Flaisher, Elad; Galalae, Razvan; Kelson, Itzhak; Keisari, Yona (Frontiers in Oncology, 2020)
Diffusing alpha-emitting radiation therapy (DaRT), employs intratumoral Ra-224 coated seeds that efficiently destroy solid tumors by slowly releasing alpha-emitting atoms inside the tumor. In immunogenic tumor models, DaRT was shown to activate systemic antitumor immunity. Agonists of the membrane-bound toll-like receptors (TLRs) enhanced these effects and led to tumor rejection. Here, we examined the combination of DaRT with agents that activate a different type of pattern recognition receptors, the cytoplasmatic RIG1-like receptors (RLRs). In response to cytoplasmatic viral dsRNA, RLRs activate an antiviral immune response that includes the elevation of antigen presentation. Thus, it was postulated that in low-immunogenic tumor models, RLR activation in tumor cells prior to the induction of their death by DaRT will be superior compared to TLR activation. Intratumoral cytoplasmatic delivery of the dsRNA mimic polyIC by polyethylenimine (PEI), was used to activate RLR, while polyIC without PEI was used to activate TLR. PolyIC(PEI) prior to DaRT synergistically retarded 4T1 triple negative breast tumors and metastases development more efficiently than polyIC, and rejected panc02 pancreatic tumors in some of the treated mice. Splenocytes from treated mice, adoptively transferred to naive mice in combination with 4T1 tumor cells, delayed tumor development compared to naïve splenocytes. Low-dose cyclophosphamide, known to reduce T regulatory cell number, enhanced the effect of DaRT and polyIC(PEI) and led to high long-term survival rates under neoadjuvant settings, which confirmed metastases clearance. The epigenetic drug decitabine, known to activate RLR in low doses, was given intraperitoneally prior to DaRT and caused tumor growth retardation, similar to local polyIC(PEI). The systemic and/or local administration of RLR activators were also tested in the squamous cell carcinoma (SCC) tumor model SQ2, in which a delay in tumor re-challenge development was demonstrated. We conclude that RIG-I-like activation prior to intratumoral alpha radiation may serve as a potent combination technique to reduce both tumor growth and the spread of distant metastases in low-immunogenic and metastatic tumor models.